The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s00192-014-2551-2
|View full text |Cite
|
Sign up to set email alerts
|

Differences in recurrent prolapse at 1 year after total vs supracervical hysterectomy and robotic sacrocolpopexy

Abstract: Women who underwent an SRH were 2.8 times more likely to have a recurrent prolapse, ≥ stage II, at 1 year, compared with those who underwent a TRH, but when composite assessment scores were used there was no difference between the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 18 publications
1
35
0
Order By: Relevance
“…The benefits of supracervical hysterectomy may reduce the risk of mesh erosion, thus avoiding cautery-induced thermal injury to the vagina [61]. Warner et al [57] observed a 4.9% mesh exposure rate for the total hysterectomy group, but no mesh exposures were seen in the supracervical hysterectomy group (p=0.03).…”
Section: Surgery For Apical Vaginal Prolapsementioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of supracervical hysterectomy may reduce the risk of mesh erosion, thus avoiding cautery-induced thermal injury to the vagina [61]. Warner et al [57] observed a 4.9% mesh exposure rate for the total hysterectomy group, but no mesh exposures were seen in the supracervical hysterectomy group (p=0.03).…”
Section: Surgery For Apical Vaginal Prolapsementioning
confidence: 99%
“…A retrospective study demonstrated that supracervical hysterectomy with sacrocolpopexy was 2.8 times more likely to result in recurrent prolapse than total hysterectomy with sacrocolpopexy, when recurrent prolapse was defined as prolapse greater than or equal to stage 2. This study did not have sufficient power to detect differences in rates of mesh exposure, with 7.5% in the total hysterectomy with sacrocolpopexy group vs. 2.3% in the supracervical hysterectomy with sacrocolpopexy group (p=0.35) [61].…”
Section: Surgery For Apical Vaginal Prolapsementioning
confidence: 99%
“…Myers et al [ 15 ] showed that women who underwent subtotal hysterectomy versus a total hysterectomy during RASC were more likely to have a recurrent prolapse (stage ≥2 of any compartment) after 1 year. No statistically bothersome symptoms were detected.…”
Section: Discussionmentioning
confidence: 99%
“…Roboticassisted total hysterectomy and sacrocolpopexy have been associated with higher rates of mesh exposure (please see complication section of paper) (41,49,50) but lower rates of recurrent anterior vaginal wall prolapse. In a retrospective cohort study of 83 women undergoing robotic supracervical versus total hysterectomy and sacrocolpopexy, those in the supracervical group demonstrated a significantly higher rate of recurrent anterior compartment prolapse (41.9% vs. 20.0%, P=0.03) (51). Similarly, in a prospective cohort study of women undergoing robotic-assisted sacrocolpopexy versus supracervical hysterectomy and cervicosacropexy, rates of recurrent anterior wall prolapse were higher in the cervical preservation group (28).…”
Section: Robotic-assisted Hysterectomy and Sacrocolpopexymentioning
confidence: 93%